How ninth graders perceive tasks with curricular overlap: The case of mathematics and chemistry - Čech, Adam; Samková, Libuše (LUMAT-B: International Journal on Math, Science and Technology Education, 2025)
This paper presents a qualitative empirical study focusing on the way in which lower-secondary school students without STEM experience perceive tasks with cross-curricular overlap, namely tasks that include both mathematics and chemistry content (ratio and stoichiometry). We prepared a worksheet with six tasks to solve and seven groups of questions to answer and assigned it to 40 ninth-graders from three different schools in a country where STEM education does not have a tradition. The study revealed that the students mostly perceive the subjects of mathematics and chemistry as distinct and tend to perceive problems with chemistry terms in the assignment as purely chemical even if a mathematical content is included in them and mathematical procedures could be used to solve them.